Pengembangan Lembar Kerja Peserta Didik Bermuatan Pertanian Industrial Jember Mata Pelajaran IPAS Kelas V SD Topik Materi Wah Ternyata Daerahku Luar Biasa - Titis Fatma Sari (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Science and Social Studies (IPAS) learning in elementary schools tends to rely heavily on textbooks and generally does not specifically incorporate the potential of particular regions or students’ local environments. As a result, students have difficulty relating IPAS material to the realities of their surrounding environment. The development of student worksheets based on Jember’s industrial agriculture is motivated by problems identified at SDN Patrang 02, where teachers still rely on textbook based teaching materials, and the worksheets used are general in nature and do not yet integrate local potential. In fact, the students’ local area, Jember, has abundant local potential, particularly in the field of industrial agriculture, with leading commodities such as tobacco, coffee, cocoa, edamame, and sugarcane. These potentials are not only regional flagship commodities but can also be utilized as contextual learning resources through the integration of local potential. This study aims to produce teaching materials that can support classroom learning while improving students’ knowledge of local potential in the field of industrial agriculture in Jember. The development model used in this study is the ADDIE model, which consists of five stages: Analyze, Design, Development, Implementation, and Evaluation. The results show that the developed student worksheets have a very high level of feasibility, with a validation score of 90.3, which falls into the very feasible category. In addition, the relative effectiveness test shows a percentage of 53.933%, which is categorized as moderate. Meanwhile, the practicality aspect based on students’response questionnaires obtained a score of 89.26, which is classified as very practical. Thus, the developed worksheets are considered valid, effective, and practical, and are suitable for use as supporting teaching materials in the learning process.
Validasi dan Finalisasi Repositori File 17 Juli 2026_Kholif Basri
Keywords: Science and Social Studies (IPAS); Student Worksheets; & Jember’s Industrial Agriculture